2020
DOI: 10.1186/s40900-020-00224-3
|View full text |Cite
|
Sign up to set email alerts
|

Exploring patient and public involvement (PPI) and co-production approaches in mental health research: learning from the PARTNERS2 research programme

Abstract: Background Patient and Public Involvement (PPI) in research is a growing field of work, incorporating experiential knowledge within research processes. Co-production is a more recent PPI approach that emphasises the importance of power-sharing to promote inclusive research practices, valuing and respecting knowledge from different sources, and relationship building. Applying co-production principles in research trials can be difficult, and there are few detailed worked examples or toolkits. This paper explores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 23 publications
1
43
0
Order By: Relevance
“…Published studies have similarly reported on the richness that emerges in the research and partnership from adopting PPIE in co-design [ 32 , 33 ]. Our work resonates with the reciprocal learning reported emphasising the importance of building the foundations for relationships, fostering trust, respect, creating a safe space, to talk about the research and the effects on the partnership [ 74 ].…”
Section: Discussionsupporting
confidence: 53%
“…Published studies have similarly reported on the richness that emerges in the research and partnership from adopting PPIE in co-design [ 32 , 33 ]. Our work resonates with the reciprocal learning reported emphasising the importance of building the foundations for relationships, fostering trust, respect, creating a safe space, to talk about the research and the effects on the partnership [ 74 ].…”
Section: Discussionsupporting
confidence: 53%
“…By involving a range of stakeholders, including young people themselves, in defining the research priorities presented here, we hope that research based within these priority areas will have a positive impact on young people’s lives and improve their mental health. There is evidence that coproduction has positive outcomes [ 10 ], but few studies have explored how coproduction is achieved in research practice [ 12 ]. We therefore recommend that further work is undertaken to monitor and evaluate the impact of coproduction on both the research process and the research findings or outputs.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, coproduction has become a popular approach in development work with young people and, most recently, in health research [ 11 ]. Within mental health research specifically, coproduction is a relatively new and innovative approach, with evidence of positive involvement and outcomes including improved mental well-being for people involved in the process [ 10 , 12 ]. The New Economics Foundation has developed six principles of coproduction that are widely used as a framework to understand coproduction [ 10 ]: Taking an assets-based approach: transforming the perception of people, so that they are seen not as passive recipients of services and burdens on the system, but as equal partners in designing and delivering services.…”
Section: Introductionmentioning
confidence: 99%
“…The role of the LEAPs and service user researchers in the PARTNERS2 programme is the subject of a separate article. 11 …”
Section: Methodsmentioning
confidence: 99%